How to take better photomicrographs: A step‐wise approach. (10th April 2018) - Cocks, Margaret; Rehman, Jamaal; Barker, Norm; Auerbach, Jena; Cowper, Shawn; Rodic, Nemanja
Abstract : The objective of our study was to establish a detailed photomicrographing protocol for pathologists and dermatopathologists using standard overhead camera and image editing packages. Through a trial‐and‐error approach we devised a series of steps that comprise our photomicrographing protocol. Descriptive and interpretive data analyses were performed to highlight how each step improves tinctorial quality of digital photomicrographs.